Aid, growth and private capital flows to Ghana - Robert Darko Osei (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This study provides an analysis of the aid-private capital flows-growth nexus for Ghana. It is premised on the argument that Ghana's new status as a middle income country plus the start of oil production is bound to result in a reduction in ODA inflows in the long term. However in the short to medium term ODA will remain an important component in the country's fiscals as well as an important tool for leveraging government policy. One of the key questions that the study addresses is how aid can be used as to reinforce the country's growth in a way that reduces its chances of being a victim of the 'oil curse'. The study makes two key observations about the economy of Ghana. First, it notes that although the structure of the economy has changed over the years, the observed change has not been of the developmentally transformative type. Production within the economy still takes place on the lower end of the technology scale and the country's exports is still dominated by primary products. Second, it notes that revenue from oil can at best replace foreign aid in the long run. However in the short to medium term, Ghana will have the complement of both oil and aid. It there behoves on the country that aid is used in an efficient and creative way so as to help improve productivity and production in agriculture and manufacturing. The study concludes by making two suggestions as to how aid can be used to help transform the economy. The first suggestion is to tackle the structural deficiency in the country's fiscals in a decisive way. The second is the need to properly prioritize public investments so as to maximize their returns.
Keywords: H60; O11; O13; 330; aid; oil production; structural change; Private Entwicklungshilfe; Wirtschaftswachstum; Erdölgewinnung; Strukturwandel; Ghana